Flavonoids-potent and versatile biologically active compounds interacting with cytochromes P450 - Hodek, Petr; Trefil, Pavel; Stiborová, Marie (Chemico-biological interactions, 2002)
Flavonoids represent a group of phytochemicals exhibiting a wide range of biological activities arising mainly from their antioxidant properties and ability to modulate several enzymes or cell receptors. Flavonoids have been recognized to exert anti-bacterial and anti-viral activity, anti-inflammatory, anti-angionic, analgesic, anti-allergic effects, hepatoprotective, cytostatic, apoptotic, estrogenic and anti-estrogenic properties. However, not all flavonoids and their actions are necessarily beneficial. Some flavonoids have mutagenic and/or prooxidant effects and can also interfere with essential biochemical pathways. Among the proteins that interact with flavonoids, cytochromes P450 (CYPs), monooxygenases metabolizing xenobiotics (e.g. drugs, carcinogens) and endogenous substrates (e.g. steroids), play a prominent role. Flavonoid compounds influence these enzymes in several ways: flavonoids induce the expression of several CYPs and modulate (inhibit or stimulate) their metabolic activity. In addition, some CYPs participate in metabolism of flavonoids. Flavonoids enhance activation of carcinogens and/or influence the metabolism of drugs via induction of specific CYPs. On the other hand, inhibition of CYPs involved in carcinogen activation and scavenging reactive species formed from carcinogens by CYP-mediated reactions can be beneficial properties of various flavonoids. Flavonoids show an estrogenic or anti-estrogenic activity owing to the structural similarity with the estrogen skeleton. Mimicking natural estrogens, they bind to estrogen receptor and modulate its activity. They also block CYP19, a crucial enzyme involved in estrogen biosynthesis. Flavonoids in human diet may reduce the risk of various cancers, especially hormone-dependent breast and prostate cancers, as well preventing menopausal symptoms. For these reasons the structure-function relationship of flavonoids is extensively studied to provide an inspiration for a rational drug and/or chemopreventive agent design of future pharmaceuticals.
Keywords: Protein Binding; inhibitory cytochromu P450; vazba proteinů; Flavonoids; systém (enzymů) cytochromů P-450; Animals; lidé; Cytochrome P-450 Enzyme Inhibitors; flavonoidy; Cytochrome P-450 Enzyme System; Humans; zvířata